Human B-cell isotype switching origins of IgE - Looney, Timothy J.; Lee, Ji-Yeun; Roskin, Krishna M.; Hoh, Ramona A.; King, Jasmine; Glanville, Jacob; Liu, Yi; Pham, Tho D.; Dekker, Cornelia L.; Davis, Mark M.; Boyd, Scott D. (Journal of allergy and clinical immunology, 2016)
B cells expressing IgE contribute to immunity against parasites and venoms and are the source of antigen specificity in allergic patients, yet the developmental pathways producing these B cells in human subjects remain a subject of debate. Much of our knowledge of IgE lineage development derives from model studies in mice rather than from human subjects. We evaluate models for isotype switching to IgE in human subjects using immunoglobulin heavy chain (IGH) mutational lineage data. We analyzed IGH repertoires in 9 allergic and 24 healthy adults using high-throughput DNA sequencing of 15,843,270 IGH rearrangements to identify clonal lineages of B cells containing members expressing IgE. Somatic mutations in IGH inherited from common ancestors within the clonal lineage are used to infer the relationships between B cells. Data from 613,641 multi-isotype B-cell clonal lineages, of which 592 include an IgE member, are consistent with indirect switching to IgE from IgG- or IgA-expressing lineage members in human subjects. We also find that these inferred isotype switching frequencies are similar in healthy and allergic subjects. We found evidence that secondary isotype switching of mutated IgG1-expressing B cells is the primary source of IgE in human subjects, with lesser contributions from precursors expressing other switched isotypes and rarely IgM or IgD, suggesting that IgE is derived from previously antigen-experienced B cells rather than naive B cells that typically express low-affinity unmutated antibodies. These data provide a basis from which to evaluate allergen-specific human antibody repertoires in healthy and diseased subjects.